Short report: Monitoring ESR1 mutations by circulating tumor DNA in aromatase inhibitor resistant metastatic breast cancer. Issue 10 (11th June 2015) - Sefrioui, David; Perdrix, Anne; Sarafan‐Vasseur, Nasrin; Dolfus, Claire; Dujon, Antoine; Picquenot, Jean‐Michel; Delacour, Julien; Cornic, Marie; Bohers, Elodie; Leheurteur, Marianne; Rigal, Olivier; Tennevet, Isabelle; et al.
<x xml:space="preserve">Abstract</x> Acquired estrogen receptor gene (ESR1) mutations have been recently reported as a marker of resistance to aromatase inhibitors in hormone receptor positive metastatic breast cancer. We retrospectively considered seven patients treated for metastatic breast cancer with available samples from the primary tumor before any treatment, cryopreserved metastasis removed during progression and concomitant plasmas. All these seven patients were in disease progression after previous exposure to aromatase inhibitors for at least 6 months, and were assessed for ESR1 mutations detection in tumor and circulating DNA. For these patients, Sanger sequencing identified four metastases with clear ESR1 mutation and one possible, whereas digital PCR identified six mutated metastases. Then, under blind conditions and using digital PCR, corresponding circulating ESR1 mutations were successfully detected in four of these six metastatic breast cancer patients. Moreover, in two patients with serial blood samples following treatments exposure, the monitoring of circulating ESR1 mutations clearly predicted disease evolution. In the context of high interest for ESR1 mutations, our results highlight that these acquired recurrent mutations may be tracked in circulating tumor DNA and may be of clinical relevance for metastatic breast cancer patient monitoring.